Association between oral health-related quality of life and atraumatic restorative treatment in school children: An exploratory study - J S Paula; LHN Tôrres; GMB Ambrosano; F L Mialhe (Wolters Kluwer Medknow Publications, 2012)
Background: The present study's objectives were to compare the perceptions of oral health-related quality of life (OHRQoL) among school children presents dental caries with that of caries-free school children, and to evaluate the subjective impact of atraumatic restorative treatment (ART) on the OHRQoL of school children. Design: Exploratory study. Setting: Public school in Piracicaba, Brazil. Materials and Methods: The sample was composed of 30 children in the age-group of 8-10 years. The children were divided into two groups: one with caries and other without caries. The information related to OHRQoL was obtained through the administration of the Child Perceptions Questionnaires (CPQ 8-10 ). To evaluate the impact of ART on the school children's OHRQoL, the CPQ 8-10 was re-administered 4 weeks after the initial treatment. For statistical analysis we used the nonparametric Wilcoxon test for two dependent variables (test and re-test groups) and the nonparametric Mann-Whitney test for independent variables (test and control groups). Results: It was observed that children with dental caries reported larger impact of oral health conditions on the quality of life when compared with the caries-free group, especially in the emotional and social well-being domains ( P≤.05). After the school children who presented with dental caries received ART, there was improvement in the median scores of CPQ 8-10 in all of the domains, but particularly in the functional limitation domain ( P≤.05). Conclusion: Dental caries exerts a strong influence on the OHRQoL of children. ART was shown to be a simple and painless caries management approach that could improve the OHRQoL of school children.